Implementasi Kurikulum Merdeka dan Tantangan Pembelajaran Tematik dalam Kurikulum Merdeka di SD N 101766 Bandar Setia (Jurnal Sadewa : Publikasi Ilmu Pendidikan, Pembelajaran dan Ilmu Sosial, 2025)
The Merdeka Curriculum was introduced as an effort to improve the quality of education in Indonesia by providing flexibility for teachers in developing more contextual and student-centered learning methods. This study aims to analyze the challenges faced by teachers in implementing the Merdeka Curriculum at SDN 101766 Bandar Setia, especially in thematic learning. The research method used is qualitative with in-depth interview techniques to one of the teachers at the school. The results showed that some of the main challenges faced include teachers' limited understanding of the optimal implementation of thematic learning, difficulties in adjusting materials to the diverse characteristics of students, and the lack of support from parents in providing learning tools and materials. In addition, limited facilities and infrastructure in schools are also an obstacle in creating a learning environment conducive to the implementation of the Merdeka Curriculum. This study concludes that although the Merdeka Curriculum gives teachers and students more freedom in the learning process, the challenges in its implementation still need to be overcome.